Developing a Qur’anic mīzān-concept for ethical assessment in mathematics learning - Nisa, Lulu Choirun; Musthofa, Musthofa; Tholchah, Muchammad (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Current mathematics assessment models prioritize academic standards over ethical values. This gap perpetuates reductionist and ethically devoid assessment. This study aims to establish a foundation for Qur'anic ethical assessment based on mizān and develop a conceptual framework for assessment in mathematics education. This theoretical-literature-thematic study analyzes five groups of the Qur'anic verses (namely: 7:85, 21:47, 42:17, 55:7-9, 57:25 ) with a critical-reflective approach to criticize the dominant culture in assessment. The analysis connects the mīzān-ethic principle with contemporary mathematical theory through an interdisciplinary synthesis. This study produces: (1) Mīzān in the Qur'an is a symbol of universal ethics. The mīzān-based assessment reflects moral values and integrity. The concept of ethical-Qur'anic assessment is a framework that unites spiritual, social, and individual aspects. (2) The concept of ethical-Qur'anic assessment should not only measure learning outcomes but also reflect the values of fairness, honesty, and balance. This assessment simultaneously and harmoniously combines cognitive, affective, and social competencies. Teachers not only test but also uphold ethical and character values. This assessment avoids bias and rejects discrimination, but fosters empathy to shape students to be active, value-conscious, and responsible individuals. This concept provides a new direction for assessment design in mathematics education.